A Novel Reverse Combination Configuration to Reduce Mismatch Loss for Stratospheric Airship Photovoltaic Arrays - Chuan Shan; Kangwen Sun; Dongji Cheng; Xinzhe Ji; Jian Gao; Tong Zou (Applied Sciences, 2024)
Enhancing the output power of stratospheric airship photovoltaic arrays during months with weak irradiance is crucial for extending the endurance of airships. Models for predicting the output power of photovoltaic arrays and the phenomenon of mismatch losses have been proposed. However, static reconstruction schemes to reduce or eliminate mismatch losses have not been studied. In this paper, an output power model for stratospheric airship arrays including the solar radiation and irradiance distribution is established. The characteristics of the irradiance distribution for the photovoltaic array (PV) are investigated through simulation. Furthermore, an innovative reverse combination configuration is developed and compared to the SP and TCT configurations in terms of performance, mismatch loss and fill factor. Finally, simulations are conducted for a full-day irradiance period of 4 days in a real wind field. The simulation results demonstrate that the proposed RC configuration significantly reduces mismatch losses and output power fluctuations, thereby enhancing the PV array’s output power. This research provides interesting insights for the design of PV array topologies for stratospheric airships.